Office hysteroscopy: back to the future!. (3rd July 2020) - Mak, J. N.; Imran, A.; Burnet, S.
Abstract: Hysteroscopy and anesthesia have come a long way in the last 150 years. While traditionally performed in the operating theater under general anesthesia, the alternative approach – so-called 'office' hysteroscopy – has gained popularity in recent years. Supporters of this modality cite the 'see and treat' capabilities, avoidance of anesthesia, more rapid turn-around time, and favorable economics as advantages. On the other hand, some question the success rate, capabilities, and patient comfort levels as potential drawbacks. In this article, we review the evidence behind all of these points as well as the requirements for setting up an office hysteroscopy service.